Glutamate 338 is an electrostatic facilitator of C–Co bond breakage in a dynamic/electrostatic model of catalysis by ornithine aminomutase. (12th February 2015) - Menon, Binuraj R. K.; Menon, Navya; Fisher, Karl; Rigby, Stephen E. J.; Leys, David; Scrutton, Nigel S.
<x xml:space="preserve">Abstract</x> How cobalamin‐dependent enzymes promote C–Co homolysis to initiate radical catalysis has been debated extensively. For the pyridoxal 5′‐phosphate and cobalamin‐dependent enzymes lysine 5, 6‐aminomutase and ornithine 4, 5‐aminomutase (OAM), large‐scale re‐orientation of the cobalamin‐binding domain linked to C–Co bond breakage has been proposed. In these models, substrate binding triggers dynamic sampling of the B12‐binding Rossmann domain to achieve a catalytically competent 'closed' conformational state. In 'closed' conformations of OAM, Glu338 is thought to facilitate C–Co bond breakage by close association with the cobalamin adenosyl group. We investigated this using stopped‐flow continuous‐wave photolysis, viscosity dependence kinetic measurements, and electron paramagnetic resonance spectroscopy of a series of Glu338 variants. We found that substrate‐induced C–Co bond homolysis is compromised in Glu388 variant forms of OAM, although photolysis of the C–Co bond is not affected by the identity of residue 338. Electrostatic interactions of Glu338 with the 5′‐deoxyadenosyl group of B12 potentiate C–Co bond homolysis in 'closed' conformations only; these conformations are unlocked by substrate binding. Our studies extend earlier models that identified a requirement for large‐scale motion of the cobalamin domain. Our findings indicate that large‐scale motion is required to pre‐organize the active site by enabling transient formation of 'closed' conformations of OAM. In 'closed' conformations, Glu338 interacts with the 5′‐deoxyadenosyl group of cobalamin. This interaction is required to potentiate C–Co homolysis, and is a crucial component of the approximately 1012 rate enhancement achieved by cobalamin‐dependent enzymes for C–Co bond homolysis.